FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN RISIKO TINGGI OBSTRUCTIVE SLEEP APNEA PADA PASIEN FIBRILASI ATRIUM - Nushrotul Lailiyya; Sobaryati Sobaryati; Novia Aiko; Chaerul Achmad (NEURONA, 2018)
FACTORS THAT INFLUENCE HIGH RISK FOR OBSTRUCTIVE SLEEP APNEA IN ATRIAL FIBRILLATION PATIENTSABSTRACTIntroduction: Atrial fibrillation (AF) is the most frequent cardiac arrhythmia in the world and associated with high morbidity and mortality. Obstructive sleep apnea (OSA) is strongly associated with AF and its prevalence is 32%-62%. Obstructive sleep apnea screening and its reduction are one approach to reduce the risk of and increasing the treatment effectiveness of AF.Aims: To determine factors that influence the high risk for OSA in AF patients.Methods: We performed a cross-sectional  analytical  and observational  study in AF patients at Hasan Sadikin Hospital, Salamun Hospital, and Ujung Berung Hospital, Bandung during period of November 2017 to January  2018. STOPBANG were used to screen OSA.Results: There were 100 subjects with age 62±12 years old, 43% male, 38% smoking, 14% obese, 16% had neck circumference ≥40cm, and majority had high risk of OSA (71%) and hypertension (74%). The factors that influence the high risk for OSA in the AF patients were hypertension, age, gender, neck circumference, and smoking.Discussion: Hypertension, age, gender, neck circumference, and smoking are related to the the high risk for OSA in AF patients.Keywords: Atrial fibrillation, obstructive sleep apnea, STOPBANGABSTRAKPendahuluan: Fibrilasi atrium (FA) merupakan gangguan irama jantung (aritmia) yang paling banyak ditemukan di dunia dan berkaitan dengan morbiditas dan mortalitas yang cukup tinggi. Obstructive sleep apnea (OSA) sangat berkaitan dengan FA dengan prevalensi 32%-62%. Skrining OSA dan berhasilnya terapi OSA pada pasien FA merupakan salah satu pendekatan untuk menurunkan risiko dan meningkatkan efektivitas tata laksana FA.Tujuan: Mengetahui faktor yang berhubungan dengan risiko tinggi OSA pada pasien FA.Metode: Penelitian analitik observasional dengan studi potong lintang pada pasien FA di Poliklinik Kardiologi RSUP Dr. Hasan Sadikin, RS Salamun, dan RS Ujung Berung, Bandung selama periode November 2017-Januari 2018. Skrining OSA menggunakan kuesioner STOPBANG.Hasil: Terdapat 100 orang subjek dengan rerata usia 62±12 tahun, 43% laki-laki, 38% merokok, 14% obesitas, 16% memiliki lingkar leher ≥40cm, serta mayoritas  berisiko tinggi OSA (71%) dan hipertensi (74%). Faktor-faktor yang memengaruhi risiko tinggi OSA penelitian secara berurutan adalah hipertensi, usia, jenis kelamin, lingkar leher, dan merokok.Diskusi: Hipertensi, usia, jenis kelamin, lingkar leher, dan merokok berpengaruh terhadap   risiko tinggi OSA pada pasien FA.Kata kunci: Fibrilasi atrium, obstructive sleep apnea, STOPBANG